A Demographic Model of Poverty among Families with Children: A Comparative Analysis of Five Industrialized Countries Based on Microdata from the Luxembourg Income Study - Janet Gornick; LaDonna Pavetti (Luxembourg Income Study (LIS), 1990)
This paper uses the LIS database to compare the probability of being poor for female-headed households and two-parent households in the United States, West Germany, Canada, Israel and Australia. This paper also uses demographics to try and explain the differences in poverty in and across each of the five countries.
Keywords: 330